Kaplan Business School’s student-centred approach: An interview with Professor James Adonopoulos (Journal of Applied Learning and Teaching, 2024)
In this wide-ranging interview, we explore the perspectives of Professor James Adonopoulos, the Academic Dean of Kaplan Business School (Australia) – one of the most reputable tertiary education providers in the field of business, globally recognised as the Business School of the Year for international students in 2023. This interview delves into Prof. Adonopoulos’s academic strategies, initiatives, and practices that have culminated in a supportive and nurturing learning environment and a humane approach to teaching.   Addressing topics related to kindness and student centricity, Prof. Adonopoulos highlights the importance of discourse-based workshops in contrast to unidirectional lectures and explains how his national team of more than 600 teachers are engaged and equipped with the skills to cultivate an engaging learning environment. Prof. Adonopoulos argues that technical skills are insufficient for the modern workplace which demands that graduates also possess a formidable set of ethical standards, emotional intelligence and cultural intelligence. He provides examples from his experiences at Kaplan Business School where he has led the creation of an inclusive, supportive, and psychologically safe academic culture that supports the emotional and intellectual growth of faculty and students. The proactive embrace of emerging technologies and the pursuit of disruptive innovation are additionally discussed in this interview with insights shared on what it means to teach and prepare students for the contemporary business world.